Productivity of tree fodder banks in a typical homegarden of Central Kerala - Patric, Anush; Raj, Asha K.; Kunhamu, T.K.; Jamaludheen, V.; Santhoshkumar, A.V. (Indian Journal of Agroforestry, 2020)
Acute scarcity of green fodder, crude protein deficit and high feeding cost are the major deterrents for profitable livestock production in homesteads. Cultivation of protein rich tree fodder banks is a promising option for overcoming feed deficit, but warrants further research to assess their productivity in homesteads with light and space constraints. The present study aimed to assess the forage yield and nutritive value of five fodder tree species viz., Morus indica (mulberry), Sesbania grandiflora (agathi), Moringa oleifera (moringa), Gliricidia sepium (gliricidia) and Calliandra calothyrsus (calliandra) under hedgerow planting (45 Ã— 45 cm spacing) in the interspaces of homegarden, in randomized block design replicated four times. The trees were harvested at 1 m height at the interval of two months during rainy season and three months during summer. Initial growth and coppice parameters were better for gliricidia, followed by agathi and calliandra. The annual green and dry forage yields were better for gliricidia (26.82 and 5.38 Mg ha-1) and calliandra (21.08 and 6.61 Mg ha-1), respectively. Gliricidia and calliandra had higher protein content and leaf-stem ratio. Agathi and mulberry showed intermediate performance with respect to yield and quality. Moringa was inferior in forage yields but rich in quality attributes like ash and mineral contents. Mulberry and calliandra showed better survival percentage. Hence, gliricidia, calliandra, and mulberry with good yield and quality are found to be ideal for hedgerow planting in the understorey of homesteads. PAR transmittance in the homestead was below 60% indicating shady nature. Pruning of overhead trees in homesteads to enhance light transmission can further elevate the yield levels of fodder banks.